ROLE, SIGNIFICANCE AND HISTORICAL STAGES OF THE LATIN LANGUAGE IN MEDICINE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article provides information on the importance and role of the science of Latin language and medical terminology in world medicine. In addition, the stage of historical development of the Latin language, its impact on world languages and its place are discussed.